Social Capital of Madura Barbers in Makassar, South Sulawesi - Jumadi, Jumadi (Komunitas, 2016)
This study aims to understand and analyze the social capital and human capital Madura ethnic barbers in Makassar. This type of research is a qualitative case study approach. The subject was a barber Madura in Makassar. Selection of informants snowball, with a focus on issues of social capital and human capital. Researcher as research instrument. The collection of data through observation, interview and documentation, analyzed by a three-stage model of water, including data reduction, data presentation, and stage of development. The validity of data through observation extension technique, perseverance, member check and triangulation. The results showed that the social capital of the aspects of trust, people have to trust how the barber Madura. Aspects of the norm, uphold the norms as Madura seacoast, and the networking aspect, the barber form a network of kinship, ethnic, economic enterprises, and through the organization of Madura in the city. Human capital barber Madura in Makassar based on knowledge gained informally by way of self-taught, environment and hereditary from parents; aspects of the experience, gained since long (hereditary) with satisfactory results; aspects of the skills needed to improve their business and customers barber; aspects of creativity, creative enough to follow the model's hair and innovation aspects of the shaver is making progress, as part of the manual (gothok) to shaving machine (clipper).